Effects of government regulatory provisions on the innovative behaviour of HEIs and economic advancement: The case of Kazakhstan. Issue 6 (December 2021) - Yembergenova, Danagul; Kumar, Ajit; Haris, Ikhfan
This study examines how government initiatives introduced in Kazakhstan's State Programme for Education Development 2011–2020 are regulated and implemented to stimulate the innovative capacity of universities. The authors then consider the implications of these changes for the government's aspiration of economic development. As government regulation is accepted as the primary explanatory factor that leads to poor performance, drawing on agency theory the study examines the combinations and conditions of existing regulatory mechanisms. Given that different agency problems are involved, the authors set out the alternatives available for the government to overcome those challenges.